Pullthrough Operation for Hirschsprung's Disease: Importance of a Circumferential (Donut) Biopsy at the Level of the Anastomosis - Susan Jehangir; Soundappan Venkatraman Sannappa Soundappan; Micheal Krivanek; Susan Arbuckle; Nicole Graf (European Journal of Pediatric Surgery Reports, 2019)
Hirschsprung's disease is characterized by the absence of ganglia in the distal colon, resulting in a functional obstruction. It is managed by excision of the aganglionic segment and anastomosis of the ganglionated bowel just above the dentate line. The level of aganglionosis is determined by performing multiple seromuscular biopsies and/or full thickness biopsy on the antimesenteric border of the bowel to determine the level of pullthrough. The transition zone is described as being irregular, and hence a doughnut biopsy is recommended so that the complete circumference can be assessed. Herein, we described a child in whom there was a selective absence of ganglion cells in 30% of the circumference of the bowel along the mesenteric border for most of the transverse colon. This case defies the known concept of neural migration in an intramural and transmesenteric fashion and emphasizes the importance of a doughnut biopsy of the pulled-down segment.